Pengaruh Intervensi Pijat Kaki Terhadap Penurunan Tekanan Darah : Systematic Review - Nursanti Anwar; Andi Masyitha Irwan; Ariyanti Saleh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: blood pressure is one of the important indicators in the cardiovascular assessment system and one's performance needs to reveal that someone who has hypertension often raises complications that cause growth such as heart disease, stroke, diabetes mellitus due to kidney disease. Many related studies that discuss reflexology are beneficial for blood pressure that iswrong with foot massage. However, previous studios presented different results related to theduration of foot massage, the right time to do blood pressure measurements and changes in bloodpressure itself. Objective: a systematic review with the aim of studying the interventions of footmassage on blood pressure by looking at these aspects, namely: the duration of foot massage, thetime of measurement and changes in blood pressure. Data Sources: This systematic review wascarried out on several international databases published from 2013 to 2018 on Pubmed, Proquest,Google Scholar and Science Direct. Method: systematic discussion is the method used in thisrenewal by conducting narrative synthesis of the main findings on interventions that can affectthe patient's blood pressure. This review is in accordance with PRISMA guidelines on discussingsystematic reviews. Results: from the 6 articles that reviewed about explaining the same resultsthat there was a significant decrease in blood pressure in the intervention group after the footmassage intervention was given